2019
DOI: 10.1103/physrevd.100.115039
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Higgs portal at the Fermilab short-baseline neutrino experiments

Abstract: The Fermilab Short-Baseline Neutrino (SBN) experiments, MicroBooNE, ICARUS, and SBND, are expected to have significant sensitivity to light weakly coupled hidden sector particles. Here we study the capability of the SBN experiments to probe dark scalars interacting through the Higgs portal. We investigate production of dark scalars using both the Fermilab Booster 8 GeV and NuMI 120 GeV proton beams, simulating kaons decaying to dark scalars and taking into account the beamline geometry. We also investigate str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 100 publications
0
47
0
Order By: Relevance
“…Similarly, KOTO provides sensitivity through the neutral decay channel K L → π 0 νν (see, e.g., the recent discussions of an anomaly in current data in [56][57][58][59][60]). The short baseline neutrino program at Fermilab will also provide new sensitivity to the Higgs portal, as recently analyzed in [55], and we exhibit the projected sensitivity for SBND and ICARUS from that reference in Fig. 1.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Similarly, KOTO provides sensitivity through the neutral decay channel K L → π 0 νν (see, e.g., the recent discussions of an anomaly in current data in [56][57][58][59][60]). The short baseline neutrino program at Fermilab will also provide new sensitivity to the Higgs portal, as recently analyzed in [55], and we exhibit the projected sensitivity for SBND and ICARUS from that reference in Fig. 1.…”
Section: Discussionmentioning
confidence: 94%
“…Exclusions from other sources (in gray) including LHCb [47], E949 K → π þ invisible [44][45][46], and CHARM S → e þ e − ; μ þ μ − [43][44][45] are shown. The 1σ and 2σ preferred contours to explain the KOTO anomaly in K L decays [56][57][58][59], and the sensitivity projections for the on-axis SBND (orange) and off-axis ICARUS (purple) experiments at Fermilab [55], are also shown for comparison (see the text for further details).…”
Section: Light Scalar Production At Lsndmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond DUNE's nominal mission to perform precision measurements of neutrino properties and neutrino oscillations, both its near and far detectors will serve as powerful probes of new physics. Recently, interest in using neutrino detectors to search for new physics has grown, with proposals to search for dark matter/dark sectors [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], millicharged particles [22][23][24], and exotic interactions among the Standard Model (SM) neutrinos [25][26][27][28][29], to name a few (see Ref. [30] for a more thorough summary of beyond-the-Standard-Model searches in neutrino experiments).…”
Section: Section 1: Introductionmentioning
confidence: 99%
“…The larger fraction of literature studied elastic scattering of relativistically produced dark matter, e.g., refs. [17][18][19][20][21], but the energetic nature of such dark matter essentially allows decent cross section for its "up"-scattering to an excited (or equivalently heavier unstable) state, under the framework of inelastic dark matter. Reference [22] pointed out the potential of detecting both the primary recoil induced by such relativistic dark matter and visible decay product(s) of the excited state and showed that it allows relevant signal searches to suffer from significantly less background contamination, hence inducing recent development in phenomenological investigations [23,24].…”
Section: Jhep07(2020)057mentioning
confidence: 99%